Poverty Reduction Support Credits : Nicaragua Country Study - Hinds, Manuel (Washington, DC: World Bank, 2017)
Nicaragua's state domination of productive capacity from the late 1970s to 1990, coupled with the civil war of the 1980s, left the economy with hyperinflation, large fiscal and current account deficits, and an external debt that was six times gross domestic product. As a result, economic activity declined at a sharp rate. By 1993, per capita income had fallen by a full 60 percent from the 1977 level. By the early 1990s the country was receiving aid equivalent to more than 70 percent of Gross Domestic Product (GDP). Subsequent administrations tried to address the country's economic problems through fiscal and monetary discipline and market-oriented reforms to redefine the role of the state. There were some successes, for example, decisive government action reduced inflation to around 10 percent by 1995, but many reforms failed due to their slow pace and to continued political volatility. The Bank supported the reform agenda with two economic recovery credit operations in the early 1990s. The results were less positive than expected, as the government's capacity to privatize state-owned enterprises and otherwise reform the public sector wavered in the face of political instability. The lack of political consensus prompted the Bank to withdraw from structural adjustment lending for several years. An opening for re-engagement was provided in 2002 when, after several failed attempts, Nicaragua successfully implemented the International Monetary Fund's (IMF) Poverty Reduction and Growth Facility (PRGF). This allowed the Bank to respond to the government's request for assistance to close a financing gap through fast disbursing budget support in the form of a programmatic structural adjustment credit. While technically a structural adjustment loan, the credit supported objectives based on budget-based goals already attained in implementing a Poverty Reduction Strategy Paper (PRSP), which had been prepared by the government in 2001. In this sense, the credit was the last structural adjustment loan and the precursor to the Poverty Reduction Support Credits (PRSCs).